Excluído da Áustria católico-nacional-socialista: sobre a autobiografia de Thomas Bernhard - Dávalos, Patricia Miranda (Contingentia, 2008)
In his first autobiographical writing, the Austrian author Thomas Bernhard attempts to show his public the reason why he became the provocative writer and outsider that he was. This paper intends to analyse how this image is constructed in the book by using a specific concept of victim as well as a provocative and subjective style. On the one hand he is successful in constructing a text in which his point of view and his personality are constantly present; on the other hand it includes diverse contradictions, which will be discussed throughout this article.